Pai Teacher's Strategy In Overcoming Bullying: Survey Study at Mulia Jaya Assa'diyyah Bintara Vocational School - Fikri, Mochammad Haziq Chairul; Syahrullah; Kunaenih (CV ODIS, 2024)
This research began with observations that the author made at Mulia Jaya Assa'diyyah Bintara Vocational School, where the author found that there were quite significant verbal bullying actions carried out by students there. So the author conducted research, which aimed to find out how PAI teachers' strategies were in dealing with verbal bullying behavior in students and wanted to know what opportunities and obstacles were in anticipating these problems. This research uses descriptive qualitative research. The subjects in this research were PAI teachers, and the supporting informants were class X and XI students. This research uses data collection techniques by observation, interviews with sources, and documentation. To check the validity of the data obtained, we used triangulation techniques by re-collecting data if there was unclear data. Based on the data generated, in implementing this strategy, PAI teachers found various opportunities, such as providing counseling guidance and forming anti-bullying policies. However, they also face obstacles such as difficulty controlling student behavior outside the classroom and students who are not easily advised.